Syntax through the looking glass: A review on two-word linguistic processing across behavioral, neuroimaging and neurostimulation studies. (November 2022) - Maran, Matteo; Friederici, Angela D.; Zaccarella, Emiliano
Abstract: In recent years a growing number of studies on syntactic processing has employed basic two-word constructions (e.g., "the tree") to characterize the fundamental aspects of linguistic composition. This large body of evidence allows, for the first time, to closely examine which cognitive processes and neural substrates support the combination of two syntactic units into a more complex one, mirroring the nature of combinatory operations described in theoretical linguistics. The present review comprehensively examines behavioral, neuroimaging and neurostimulation studies investigating basic syntactic composition, covering more than forty years of psycho- and neuro-linguistic research. Across several paradigms, four key features of syntactic composition have emerged: (1) the rule-based and (2) automatic nature of the combinatorial process, (3) a central role of Broca's area and the posterior temporal lobe in representing and combining syntactic features, and (4) the reliance on efficient bottom-up integration rather than top-down prediction. Highlights: Two-word linguistic structures capture the key aspects of syntactic composition. We provide a comprehensive review of behavioral, neuroimaging and neurostimulation studies on two-word syntactic composition. Syntactic composition is an automatic and rule-based process. These operations are supported by Broca's area and the posterior temporal lobe. Bottom-up integration emerges as a key feature of syntactic composition.